Transformation in a New Key: Music in Vids and Vidding. Issue 2 (December 2015) - Turk, Tisha
Abstract : 'Vids', a genre of remix that began as slideshows and VHS tapes and is now a widespread digital practice, combine clips from movies or television with carefully chosen music (usually popular songs) to celebrate, interpret, or critique the video source. Vids are defined by music: vidders' use of music helps to distinguish vids and the vidding tradition from other forms of remix video. Yet most fan studies scholarship on vidding has focused on vids' relationships with their visual source texts and paid relatively little attention to music. In contrast, I argue that music plays a key role in both the creative processes of vidders and the rhetorical and emotional effects of vids on their intended audiences. And, in addition to contributing to vids' transformations of their visual source material, music is itself transformed through integration into a vid. This analysis suggests that – at least for their intended audiences – vids do constitute transformative and thus fair use of copyrighted music.